Survivorship of Patellofemoral Osteochondral Allograft Transplantation - Eric J. Cotter, M.D; David R. Christian, B.S; Rachel M. Frank, M.D; Eildar Abyar, M.D; Dillen Wischmeier, B.A; Adam B. Yanke, M.D., Ph.D; Jack Farr, M.D; Brian J. Cole, M.D., M.B.A (Elsevier, 2019)
Introduction: We performed a survivorship analysis of patients treated with patellofemoral osteochondral allograft transplantation (OCA) using either a shell or plug technique and identified variables associated with graft failure. Methods: Consecutive patients at two institutions who underwent OCA of the patellofemoral compartment between March 1, 2001 to March 1, 2015, were retrospectively identified at minimum 2 years' follow-up. Demographic information, intraoperative findings, and postoperative data were collected. Patients were divided into two groups on the basis of surgical technique (plug group and shell group). Failure was defined as revision OCA, conversion to arthroplasty, or gross appearance of graft degeneration on second-look arthroscopy. Logistic regression analysis was performed to identify patient- and surgery-specific variables associated with survivorship. Results: Fifty patients were identified (36 women and 14 men; mean age 37.43 ± 8.87 years). Sixteen patients received plug allografts, whereas 34 received shell allografts. Forty percent of patients underwent a concomitant meniscal, ligamentous, malalignment, or chondral procedure. Five patients in the Plug Group (31.3%) underwent reoperation at a mean 1.37 ± 1.34 years, and 28 patients (82.4%) who received Shell OCA underwent reoperation at a mean 1.94 ± 1.92 years. Two patients in the plug group had graft failure at a mean 9.17 ± 0.93 years, whereas 13 patients in the shell group had graft failure at a mean 3.81 ± 2.78 years. Patients with plug allografts demonstrated 100% and 66% survival at 5 and 9.8 years, respectively. For the shell group, survivorship was 65.8% and 37% at 5 and 10.6 years, respectively. Increasing body mass index was associated with failure for the case series overall (odds ratio 1.33, P = .020). Traumatic cause was found to be protective of failure (odds ratio = 0.02, P = .035). Conclusions: Plug OCA of the patellofemoral compartment can be an efficacious procedure with quality mid-term outcomes. Shell OCA led to high failure rates at midterm outcomes. Increasing body mass index may predispose patients to failure, whereas traumatic cause of their lesion was associated with improved outcomes. Level of Evidence: Level IV, Therapeutic case series.